New Directions for Boundaryless and Protean Careers What do Human Resources Managers Make Differently? - Onay, Meltem; ATASEVEN, BURÇİN (My University, 2010)
This study seeks to present a guideline to human resources managers in order to help them while planning their employees’ careers. Survey method was conducted to 223 employees in foreign invested and domestic companies in order to determine their career attitudes (valuesdriven career attitude, self-directed career attitude, organizational mobility and boundaryless mindset), personality characteristics (career authenticity, openness to experience, proactive personality, goal orientation), and demographic indicators (gender, age, marital status, education, having children, job status, job turnover, organization tenure, job tenure). Our research consists of three sections. In first section there were no differences between foreign invested and domestic companies based on career attitudes preferences. In second section the results found support for that the people with “career authenticity” and “goal orientation” prefer “psychological satisfaction” while the people with “proactive personality” and “openness to experience” prefer “physical satisfaction”. In last section there were differences only between age groups and employees having children based on their career attitudes and personality characteristics.
Keywords: Çalışanlar; Performans--Yönetim; Performans Ölçümü; Kişilik Özellikleri; Employees; Performance--Management; Performance Measurement; Personality Characteristics